Synthesis of Cationic Silver Nanoparticles with Highly Potent Properties against Oral Pathogens and Their Biofilms. Issue 3 (23rd January 2023) - He, Yanping; Ketagoda, Don Hashan Kevin; Bright, Richard; Britza, Susan Marie; Zechner, Joshua; Musgrave, Ian; Vasilev, Krasimir; Zilm, Peter
Abstract: Dental caries is a major disease associated with the proliferation of acidogenic bacterial species such as Streptococcus mutans that are part of the commensal microbiota of the mouth. Silver nanoparticles (AgNPs) are attractive antibacterial agents as they target multiple sites in bacteria which reduces antimicrobial resistance. In this study, we synthesised stable, highly positively charged AgNPs capped with branched PEI (BPEI‐AgNPs) and characterized them using UV–vis absorption, transmission electron microscopy (TEM), the size of which were approximately 7.5 nm. The antibacterial activity and anti‐biofilm capacity of BPEI‐AgNPs was investigated against cariogenic bacteria. Our results demonstrated that BPEI‐AgNPs are potent clinical oral antiseptics. The cytotoxicity of the BPEI‐AgNPs was also studied against two mammalian cell lines. The results indicated that BPEI‐AgNPs were non‐cytotoxic and were safer than commercially used dental antiseptics. We conclude that the BPEI‐AgNPs are safe for oral clinical application and are an effective oral antimicrobial agent. Abstract : Silver nanoparticles (AgNPs) target multiple sites in bacteria which reduces antimicrobial resistance. We synthesised highly positively charged AgNPs capped with branched PEI (BPEI‐AgNPs). Our results demonstrated that BPEI‐AgNPs are potent clinical oral antiseptics and non‐cytotoxic. We conclude that the BPEI‐AgNPs are an effective oral antimicrobial agent.